Interference in the determination of 24 biochemical constituents in the ADVIA 1800 autoanalyzer caused by in vitro addition of commercial emulsion used in parenteral nutrition to a sera pool - Saldaña Orejón, Italo Moisés (2016)
Introduction. The analytical interference due to turbidity may cause clinically significant errors in the results of biological magnitude. Objectives. To identify and quantify turbidity (lipemia) possible interference in the routine measurement of 24 biochemical constituents using clinically relevant interference criterion when the maximum desirable systematic error is exceeded. Design. Experimental study with pre and post-test. Setting. Hospital Edgardo Rebagliati Martins, Lima, Peru. Biological material: Pooled sera from samples processed at the central laboratory of the hospital. Interventions. Increasing amounts of a parenteral nutrition commercial lipid emulsion were added to seven different aliquots of a pool of sera, and the influence of interference in 24 constituents was determined by triplicate. The Spanish Society of Clinical Chemistry guideline was followed. Main outcome measures. Lipemia-influenced constituent concentration relative percent deviation, compared with a sample without interference. Results. The constituents glucose, creatinine, potassium, total cholesterol, HDL cholesterol, alkaline phosphatase, gamma glutamyl transferase, amylase and lipase showed no interference in all aliquots with increasing concentrations of the assay interference. Interference was observed in urea, uric acid, total protein, albumin, total bilirubin, cholesterol LDL, transferrin, phosphorus, iron, lactate dehydrogenase, aspartate aminotransferase, alanine aminotransferase, creatine phosphokinase, calcium and magnesium. Conclusions. Of the 24 constituents studied, 15 had clinically significant interference. It is recommended that each laboratory investigates the effects of this interference using their own methods, reagents and instruments.